El rincón de lectura en el desarrollo de la inteligencia emocional en los niños y niñas del nivel inicial II, de 4 a 5 años paralelo “A” del centro de educación inicial Carlota Noboa de Durango, cantón Guaranda, provincia Bolívar, año 2023 - Benítez Ango, Lizeth Yolanda (2024)
The reading corner is an educational strategy aimed at promoting the development of emotional intelligence in children from 4 to 5 years old. Emotional intelligence refers to the ability to recognize, understand, and regulate emotions both one's own and those of others. This project aims to establish how the reading corner helps the development of emotional intelligence in such a way that it allows to promote the habit of reading and strengthen the emotional skills of children through interaction with different types of texts and related activities. Therefore, the reading corner becomes a special space within the classroom, where students can explore and enjoy books, stories and various activities related to reading. Within the activities in the reading corner, the development of emotional intelligence is promoted, which occurs through dramatizations, discussion of emotions present in the story, drawing, among others. In addition, empathy and reprimand towards others are encouraged by sharing books or resources that generate emotions. As a result, it is expected that the proposal of our work will be a strategy where children develop emotional or basic skills such as the expression of emotions, recognition of the emotions of the other, emotional regulation and empathy. These skills are fundamental for the integral development of children, and that allows them to properly manage their emotions and establish healthy social relationships.